Wound care practices across two acute care settings: A comparative study. Issue 5 (27th December 2019) - Gillespie, Brigid M.; Walker, Rachel; Lin, Frances; Roberts, Shelley; Eskes, Anne; Perry, Jodie; Birgan, Sean; Nieuwenhoven, Paul; Garrahy, Elizabeth; Probert, Rosalind; Chaboyer, Wendy
Abstract: Aims and objectives: Describe and compare current surgical wound care practices across two hospitals in two health services districts, Australia. Background: Surgical site infections (SSI) are a complication of surgery and occur in up to 9.5% of surgical procedures, yet they are preventable. Despite the existence of clinical guidelines for SSI prevention, there remains high variation in wound care practice. Design: Prospective comparative design using structured observations and chart audit. Methods: A specifically developed audit tool was used to collect data on observed wound care practices, documentation of wound assessment and practice, and patients' clinical characteristics from patients' electronic medical records. Structured observations of a consecutive sample of surgical patients receiving wound care with a convenience sample of nurses were undertaken. The manuscript adheres to the Strengthening the Reporting of Observational Studies in Epidemiology (STROBE) Statement. Results: In total, 154 nurses undertaking acute wound care and 257 surgical patients who received wound care were observed. Across hospitals, hand hygiene adherence after dressing change was lowest (Hospital A: 8/113, 7%; Hospital B: 16/144, 11%; χ 2 : 8.93, p = .347). Most wound dressing practices were similar across sites, except hand hygiene prior to dressing change (Hospital A: 107/113, 95%; Hospital B: 131/144, 91%; (χ 2 : 7.736, p = .021) and use of clean gloves using nontouch technique (Hospital A: 88/113, 78%; Hospital B: 90/144, 63%; χ 2 : 8.313, p = .016). The most commonly documented wound characteristic was wound type (Hospital A: 43/113, 38%; Hospital B: 70/144, 49%). What nurses documented differed significantly across sites ( p < .05). Conclusions: Clinical variations in wound care practice are likely influenced by clinical context. Relevance to clinical practice: Using an evidence‐based approach to surgical wound management will help reduce patients' risk of wound‐related complications.